2021
DOI: 10.18632/aging.202288
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping of immune and endometrial epithelial cells in endometrial carcinomas revealed by single-cell RNA sequencing

Abstract: Tumors are complex ecosystems harboring multiple cell types which might play a critical role in tumor progression and treatment response. The endometrial epithelial cell identities and immune microenvironment of endometrial carcinoma (ECC) are poorly characterized. In this study, a cellular map of endometrial carcinoma was generated by profiling 30,780 cells isolated from tumor and paratumor tissues from five patients using single-cell RNA sequencing. 7 cell types in lymphocytes, 7 types in myeloid cells and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Our previous study [15] also indicated high lymphocytes in ltration in an MMR-D cancer tissue whose MSH6 expression is negative (Figure S2A). The existence of different tumor-in ltrating immune cell types in this sample was also assessed by immunohistochemistry (IHC) staining with CD3, CD8, CD20, CD68 and CD163 antibody (Figure 5A).…”
Section: Cell Mapping Of Immune Ecosystem In An Mmr-d Ec Samplementioning
confidence: 54%
See 1 more Smart Citation
“…Our previous study [15] also indicated high lymphocytes in ltration in an MMR-D cancer tissue whose MSH6 expression is negative (Figure S2A). The existence of different tumor-in ltrating immune cell types in this sample was also assessed by immunohistochemistry (IHC) staining with CD3, CD8, CD20, CD68 and CD163 antibody (Figure 5A).…”
Section: Cell Mapping Of Immune Ecosystem In An Mmr-d Ec Samplementioning
confidence: 54%
“…Single-cell RNA-seq data of EC5-T in PRJNA650549 were downloaded from the SRA database (https://www.ncbi.nlm.nih.gov/sra/PRJNA650549). We used the Cell Ranger software pipeline (version 2.2.0, 10xGenomics) to process raw sequencing data and Seurat (version 2.3.4) R package for downstream analysis as previously described [15]. Brie y, principle component analysis (PCA) was performed for dimensional reduction.…”
Section: Single-cell Transcriptome Data Collection and Analysismentioning
confidence: 99%
“…Following resection, a representative tumor fragment was isolated and transferred rapidly to the laboratory for study as previously described [ 20 ]. Briefly, tissue was initially cut into segments and subjected to digestion by collagenase type I/II (Thermo Fisher Scientific, USA) and DNAse I (Sigma, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study also indicated higher lymphocytes infiltration in an MMR-D cancer tissue compared to other (MMR-I) samples [20]. To gain deeper insight into the immune cellular composition and phenotypic diversity of MMR-D endometrial cancer, we profiled 3371 cells obtained from an MMR-D EC sample (labeled "EC-MSI") using the single-cell RNA-seq (10X Genomics platform).…”
Section: Cell Mapping Of Immune Ecosystem In An Mmr-d Ec Samplementioning
confidence: 99%
“…That allows an unprecedented dissection of transcription within millions of individual cells. Both single-cell RNA sequencing (scRNA-seq) and single-nucleus RNA sequencing (snRNA-seq) have exciting applications [65][66][67][68][69][70][71][72][73][74][75][76][77], for instance: (i) discovering and characterizing cell type in health and diseases, such as cancer [13,[78][79][80][81][82][83][84][85][86][87][88][89], with implications in immunology [90], immune-mediated diseases [91], immunotherapy [92][93][94][95][96][97][98][99][100] and drug resistance [101]; (ii) deciphering the roles of such specific cell types in health and disease [102], including mitochondrial heteroplasmy [33]; and (iii) analyzing cell emergence, development and plasticity in tissues and organisms. These studies are also applied to study plant biology [103,104].…”
Section: Functional Genomicsmentioning
confidence: 99%